THE EFFECTIVENESS OF VILLAGE GOVERNMENT COMMUNICATION WITH COMMUNITY IN PROVIDING SOCIAL ASSISTANCE DURING COVID-19 PANDEMIC AT RAHARJA VILLAGE WONOSARI DISTRICT - herlina hasan; Titin Dunggio; Ely Ibrahim (Journal of Economic, Business, and Administration (JEBA), 2022)
This research aims to determine the effectiveness of village government communication with the community in providing social assistance during the COVID 19 pandemic in Raharja Village, Wonosari District.Method in this research is a type of descriptive qualitative research. Qualitative approach is a research method that is directed at understanding social phenomena from the participant's perspective, by interviews, observation and documentation steps.Result showed that the village government communication with the community wasquite effective, but it still needs to be improved so that the community felt satisfied with the way of communication carried out by the village government in providing social assistance where the COVID-19 pandemic was in Raharja village, Wonosari district. The factors that hinder the effectiveness of village government communication with the community in providing social assistance in Raharja Village were the village government's ability to communicate, the language style used by the village government in conveying information to the community was still unclear, and different messages.